(untitled) (Research, Society and Development, 2022)
With the growing demand of food consumption and, consequently, of industrialized products, manufacturers began to apply a large amount of chemical additives, aiming to reduce production costs, as well as to meet consumer expectations. In this way, the members of the Tutorial Education Program - PET Chemistry of the Federal Institute of Paraíba - IFPB, Campus João Pessoa, developed a research activity with the purpose of approaching the problem "Food additives", in line with the teaching of Chemistry. The study was developed in a class of the 9th grade of Elementary School, at Escola Cidadã Integral (ECI) José Lins do Rego, located in the municipality of Pilar, Paraíba, Brazil. The application took place remotely, through the online transmission platform "Google Meet", and 12 (twelve) students participated in the survey. The methodologies used were qualitative and participatory, and data collection took place through a Survey Instrument (IS) and a Playful Assessment Instrument (IAL), built in “Google Forms”. The results obtained were promising, since the debate stimulated the exchange of empirical knowledge among the students, as well as the perception of the consumption of food additives in their daily lives, and the experiment presented confirmed the theory presented in the classroom.